2017
DOI: 10.3389/fpsyg.2017.01861
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Engagement Mediates the Relationship between Positive Life Events and Positive Emotionality

Abstract: Need for Cognition (NFC) is conceptualized as an individuals’ tendency to engage in and enjoy effortful cognitive activity and, thus, captures one’s cognitive engagement. It plays a well-established role in information processing in experimental or academic contexts. However, so far comparably little is known about its consequences for other than purely cognitive or academic outcomes. Indeed, NFC is positively associated with personality traits pertaining to Positive Emotionality (PE) and negatively to traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The relation to effective resource allocation refers to processes that may further contribute to the understanding of how NFC is related to emotional adjustment. The finding of increased effort to control with higher NFC levels is in line with previous research that suggested active behavior to cope with demanding situations as explanation for associations between NFC and subjective well-being (e.g., [15]). From an application-oriented perspective, individuals with higher NFC levels may be better able to implement intentions to adjust on emotional challenges in their everyday life.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relation to effective resource allocation refers to processes that may further contribute to the understanding of how NFC is related to emotional adjustment. The finding of increased effort to control with higher NFC levels is in line with previous research that suggested active behavior to cope with demanding situations as explanation for associations between NFC and subjective well-being (e.g., [15]). From an application-oriented perspective, individuals with higher NFC levels may be better able to implement intentions to adjust on emotional challenges in their everyday life.…”
Section: Discussionsupporting
confidence: 90%
“…It is related to academic achievement and decisional processes [5,7,12], but clearly distinguishable from intelligence [5,9,10,13]. There is also some evidence linking NFC to desirable non-cognitive outcomes like positive emotionality, affective adjustment, and self-esteem (e.g., [10,14,15]). For example, individuals with higher NFC levels report to be more satisfied with their studies [16] and with their life in general [17].…”
Section: Introductionmentioning
confidence: 99%
“… 2 Please note that some results from this subsample were already reported in a paper by Strobel, Anacker, and Strobel (2017) that was originally planned as a follow-up paper on the present report. That paper is on a potential mediating role of NFC in the relationship of positive life events with positive emotionality.…”
mentioning
confidence: 65%
“…To follow-up on these intriguing results, we (1) aimed at a conceptual replication of these findings and (2) extended the examination to Need for Cognition (NFC), an investment trait conceptually closely related to Openness/Intellect (e.g., Fleischhauer et al, 2010). To this end, we used an existing data set that had been collected from the general population of Dresden, Germany, during a research project on the neurogenetics of personality, results of which have in part already be reported (Anacker, Enge, Reif, Lesch, & Strobel, 2013; Strobel, Anacker, & Strobel, 2017). The study comprised several assessments that involved: (a) blood sampling for later genetic analyses and the assessment of personality traits; (b) self-reports on negative life events (NLE) in a smaller subsample; and (3) self-reports on positive life events (PLE) and NLE assessed several months later in an again smaller subsample.…”
Section: Starting Point Of the Present Workmentioning
confidence: 99%
“…Cazan & Indreica, 2014;Elias & Loomis, 2002;Grass et al, 2017;Sadowski & Gülgös, 1996). Only in recent years, the question was brought up to what extent NFC could be helpful not only in cognitive challenges but also in overcoming challenges in a broader sense (Bye & Pushkar, 2009;Strobel et al, 2017). These challenges are important to the concept of wellbeing, which has been described as a state in which "individuals have the psychological, social, and physical resources they need to meet a particular psychological, social, and/or physical challenge" (Dodge et al, 2012, p. 230).…”
Section: Introductionmentioning
confidence: 99%